Protecting Indonesia's Communal Intellectual Property Rights: A TWAIL Perspective - Putri, Ria Wierma; Sabatira, Febryani; Kasmawati, Kasmawati; Hanumsari, Shafa Raida A. (Uti Possidetis: Journal of International Law, 2024)
The Third World Approach to International Law (TWAIL) emerges as a critical perspective on the current international legal system, providing a robust framework to aid Indonesia in safeguarding its communal intellectual property rights. This research seeks to emphasize the urgency of adopting TWAIL and elucidates how its application can play a pivotal role in advancing both economic prosperity and social identity in Indonesia. Positioned within a normative juridical framework, this study delves into the TWAIL perspective and its relevance to the protection of Communal Intellectual Property Rights (CIPR). It demonstrates how embracing the TWAIL approach for communal intellectual property rights can establish a legal framework that is more just, inclusive, and respectful of the rights of indigenous communities. By securing strong legal protections at both international and national levels, communities gain the ability to manage their traditional knowledge for commercial use, identifying potential global markets. Consequently, this approach fosters improvement and underscores the potential positive impacts on economic development, particularly in expanding markets and accessing goods.